Research on Scholarly Publishing Based on Artificial Intelligence Environments - Xia, Liying (International Journal of Computer Science and Information Technology, 2024)
With the rapid development of digital technology, the academic publishing field is facing transformation and challenges. This paper explores the impact of digital transformation on traditional publishers against the background of China's academic publishing market. By analyzing the development status of digital publishing and market trends, it puts forward the suggestion that traditional academic publishers should seize the opportunity of the integration of artificial intelligence and digital technology to accelerate digital transformation. In the current competitive digital publishing era, academic publishers should focus on both specialization and scaling to enhance their competitiveness and market position and promote the academic publishing field to intelligent and convergent development, so as to achieve the goal of long-term sustainable development.